Bone mineral density and muscle mass associated with healthy eating index in postmenopausal women; results from RaNCD cohort study - Negin Kamari; Hawal Lateef Fateh; Yahya Pasdar; Shahab Rezaeian; Ebrahim Shakiba; Farid Najafi (BMC, 2023)
Abstract Background The Healthy Eating Index 2015 (HEI-2015) is a tool for checking the quality of diet. This index is used to examine how well people's dietary behavior fits certain criteria for achieving a healthy diet in Dietary Guidelines for Americans 2015-2020. We look at the possible association between the HEI-2015 and bone mineral density (BMD) and muscle strength in postmenopausal women. Methods This research included 1012 postmenopausal women from the recruitment phase of the Ravansar Noncommunicable Diseases (RaNCD) cohort study in Kermanshah-Iran. A standardized and repeatable food-frequency questionnaire (FFQ) that contains 118 items was used to quantify dietary consumption. Anthropometric indices measured via Bio-Impedance Analyzer BIA (Inbody 770, Inbody Co, Seoul, Korea). Result The mean age of postmenopausal women was (56.41 ± 5.31) years. Participants in the highest quartile had a more daily energy intake compared to the lowest quartile (2329.89 ± 837.59), (P < 0.001). Women in the upper quartiles had greater Skeletal Muscle Mass (SMM) than those in the lower quartiles (21.61 ± 2.80 vs 20.52 ± 3.13; p = 0.0002). The linear model didn't show a significant relationship between HEI score and greater BMD (β = 0.0014, P = 0.169). Conclusion A diet of high quality followed by a high HEL-2015 score was shown to be strongly connected to increased BMD and muscle mass in Kurdish postmenopausal women.